1989
DOI: 10.1161/01.cir.80.5.1137
|View full text |Cite
|
Sign up to set email alerts
|

Ventricular expression of atrial natriuretic polypeptide and its relations with hemodynamics and histology in dilated human hearts. Immunohistochemical study of the endomyocardial biopsy specimens.

Abstract: To investigate the mechanism of expression of atrial natriuretic polypeptide (ANP) in human ventricles, we conducted an immunohistochemical study of ANP in biventricular endomyocardial biopsy specimens obtained from a total of 49 patients with cardiac dilatation due to dilated cardiomyopathy (21 patients), postmyocarditis (18 patients), or volume overload (five patients) and subjects with no dilatation as controls (five patients). Four-micron thick sections were stained by an indirect immunoperoxidase method u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0
1

Year Published

1990
1990
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(17 citation statements)
references
References 14 publications
2
14
0
1
Order By: Relevance
“…There was a significant correlation between both methods (r = 0.69, P < 0.05) (Fig. 5 A) (44)(45)(46). Conversely, the very low expression of ANF in our nonfailing tissues support the notion that the samples of these 'donors' were indeed normal.…”
Section: Resultsmentioning
confidence: 90%
“…There was a significant correlation between both methods (r = 0.69, P < 0.05) (Fig. 5 A) (44)(45)(46). Conversely, the very low expression of ANF in our nonfailing tissues support the notion that the samples of these 'donors' were indeed normal.…”
Section: Resultsmentioning
confidence: 90%
“…It develops as multiple intracavitary or intramural nodules found mostly in the ventricles, undergoes spontaneous regression, and is frequently associated with tuberous sclerosis and other congenital malformations and neoplasms [2,11,16,27]. For these reasons with the histological and ultrastructural findings, most investigators have proposed that CR is a hamartoma of fetal cardiac myocyte (synonymous with developmental abnormality, congenital malformation, or arrested cardiac myocyte maturation) [17,34,35]. Other speculations have included a neoplasm of cardiac myocyte or Purkinje cell (Purkinjeoma), glycogen storage disease, cellular gigantism, and dysplasia [2,5,13].…”
Section: Introductionmentioning
confidence: 99%
“…Bloch et al (1986) have suggested that neonatal ventricular cells utilize a constitutive pathway for ANP release because they lack secretory granules characteristic of atrial cardiocytes, which store the peptide before secretion. However, the presence of ANP granules in hypertrophied ventricular tissue (Ding et al, 1987;Tsuchimochi et al., 1988;Edwards et al, 1988;Gu et al, 1989;Mercadier et al, 1989;Takemura et al, 1989) suggests that a segretagogue could enhance ANP release from ventricular cells by a regulatory pathway analogous to that in atria.…”
Section: Introductionmentioning
confidence: 99%